Au/SBA-15 catalyst prepared by ozone treatment and importance of negatively charged gold in CO oxidation by DRIFTS. (July 2020) - Feng, Xiaoqing; Meng, Dan; Yang, Yong; Tan, Zhaoyi; Liang, Jinhu; Xiao, Chao
Abstract: There is a lack of consensus on the charge state of active gold species in catalytic CO oxidation reaction. Herein, Au/SBA-15 catalyst was prepared by room temperature ozone treatment. Through diffuse reflectance Fourier-transform infrared spectroscopy (DRIFTS), two different gold species, Au 0 and Au δ− with CO adsorption at about 2112 cm −1 and 2077 cm −1, were observed on Au/SBA-15. In CO oxidation mixture, the 2077 cm −1 band is completely attenuated while the 2112 cm −1 band retains some intensity. CO–Au δ- bonding is weaker than that of CO–Au 0, but CO–Au δ- exhibits higher reactivity towards oxygen. Ozone treatment produces AuOx nanoparticles that is not stable and decomposes to metallic Au gradually. To our best knowledge, this is the first time to identify the presence and importance of Au δ− species for "inert" SiO2 supported gold catalyst. Graphical abstract: Image 1 Highlights: Au/SBA-15 prepared through room temperature ozone treatment. CO–Au δ- bonding is weaker than that of CO–Au 0, but with higher reactivity towards oxygen.